2020
DOI: 10.1111/os.12665
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Dislocation After Total Hip Arthroplasty in Patients with Crowe Type IV Developmental Dysplasia of the Hip

Abstract: Objective: To investigate whether the risk of dislocation after total hip arthroplasty (THA) in patients with Crowe type IV developmental dysplasia of the hip (DDH) is high and to further identify the risk factors for postoperative dislocation in these patients.Methods: This retrospective cohort study reviewed Crowe type IV DDH patients undergoing THA between January 2009 and December 2017 in our institution. Each Crowe type IV DDH patient was matched with three Crowe type I, II, or III DDH patients according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 44 publications
0
27
0
1
Order By: Relevance
“…Regarding the limitation of the thin polyethylene liner and extremely small femoral head, standard-sized component with ceramic-on-ceramic bearing is recommended in recent studies [13,12,10]. Quantitative coverage analysis suggested that segmental de ciency located at the entire acetabular rim, excepted for the posterior direction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the limitation of the thin polyethylene liner and extremely small femoral head, standard-sized component with ceramic-on-ceramic bearing is recommended in recent studies [13,12,10]. Quantitative coverage analysis suggested that segmental de ciency located at the entire acetabular rim, excepted for the posterior direction.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the severe dysplasia of the hip, the use of small acetabular prosthesis was recommended to achieve satisfactory bony coverage [7,8]. However, polyethylene wear and risk of postoperative dislocation have been proved to be associated with small prosthesis size [9][10][11]. Follow-up studies of high-riding DDH also showed that acetabular revision risk was signi cantly higher than femoral revision [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al . reported that use of a larger femoral head and improved abductor muscle strength could help reduce the rate of postoperative dislocation 43 . A 28‐mm ceramic femoral head was used in all the bilateral Crowe type IV DDH following the method we introduced.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al reported that use of a larger femoral head and improved abductor muscle strength could help reduce the rate of postoperative dislocation. 43 A 28-mm ceramic femoral head was used in all the bilateral Crowe type IV DDH following the method we introduced. Due to the morphologic abnormalities in the acetabulum and the femur, placing the prosthesis at an ideal location is difficult and soft tissue balance is necessary.…”
Section: Postoperative Complications In Crowe Type IV Developmental Dmentioning
confidence: 99%
“…Rates of intraoperative fracture, postoperative dislocation, and nerve injury were 2.7%, 4.8%, and 1.1%, respectively. Previous studies [ 18 22 ] have reported intraoperative fracture rates as high as 28%, postoperative dislocation rates ranging from 1% to 17%, and nerve injury rates of approximately 10%. These comparisons indicate that the decision-making in the present study was appropriate and can be used as the basis for establishing a predictive model.…”
Section: Discussionmentioning
confidence: 99%